A Bibliometric Review of the Development of Entrepreneurship: Literature Analysis, Conceptual Changes, and Implications for Contemporary Business Transformation - Afdhal Chatra; Ahmad Rizani; Yovita Yovita; Saputra Adiwijaya (West Science Journal Economic and Entrepreneurship, 2023)
This research investigates the landscape of entrepreneurship literature through a comprehensive analysis that integrates bibliometrics and keyword examination. Utilizing VOSviewer for bibliometric analysis, influential works, thematic clusters, and intellectual relationships are identified, offering a macroscopic view of the field's evolution. Concurrently, a keyword analysis illuminates prevalent themes, shedding light on the interdisciplinary nature of entrepreneurship studies. The results reveal a dynamic landscape characterized by foundational concepts, emergent trends, and a commitment to addressing societal challenges. Key themes include entrepreneurship education, economic and social development, sustainability, and gender considerations. The findings provide valuable insights for researchers, practitioners, and policymakers, guiding future research directions and informing strategies for fostering entrepreneurship in diverse contexts.